TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK JUAL BELI IKAN DENGAN SISTEM PANCING: Studi Kasus Di Pemancingan Andalan Jaya Dan Kampung Batik Di Kecamatan Tamanan Kabupaten Bondowoso - Mohammad Firmansyah; Qurrotun A’yuni (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
In the practice of buying and selling, people sometimes ignore things that could be detrimental to each other. The loss is related to the object or to the property. This loss is due to ignorance or obscurity of the sale and purchase. Buying and selling fish in Tamanan District, Bondowoso Regency, namely buying and selling that contains elements of ambiguity (gharar) for objects that have been traded. Neither the seller nor the buyer can confirm the form of the object being traded based on the purpose of the contract, namely the sale and purchase of fish using the